2022
DOI: 10.3390/jcm11102775
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Low-Intensity Extracorporeal Shock Wave Treatment in Erectile Dysfunction Following Radical Prostatectomy: A Systematic Review and Meta-Analysis

Abstract: Erectile dysfunction (ED) is a well-known complication of radical prostatectomy (RP). Oral 5-phosphodiesterase inhibitors are currently the most widely used penile rehabilitation treatment for ED following RP, but they are less effective than for those with general ED. Low-intensity extracorporeal shock wave treatment (LI-ESWT), causing a biological change that induces neovascularization, has recently been used as a treatment for ED. Therefore, we conducted a systematic review and meta-analysis to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
0
8
0
3
Order By: Relevance
“…conducted a recent systematic review and meta-analysis of LISWT following RP and reported IIEF scores 3–4 months post-BNSRP were statistically better than the control (weight mean difference = −5.37, p = 0.02). 53 Although, two studies in their analysis found no significant difference at 9–12 months post-LISWT. Despite a low level of evidence among the five studies in their analysis, these data suggest LISWT may have a statistically significant impact on early EF recovery post-BNSRP.…”
Section: Penile Rehabilitation Interventionsmentioning
confidence: 93%
“…conducted a recent systematic review and meta-analysis of LISWT following RP and reported IIEF scores 3–4 months post-BNSRP were statistically better than the control (weight mean difference = −5.37, p = 0.02). 53 Although, two studies in their analysis found no significant difference at 9–12 months post-LISWT. Despite a low level of evidence among the five studies in their analysis, these data suggest LISWT may have a statistically significant impact on early EF recovery post-BNSRP.…”
Section: Penile Rehabilitation Interventionsmentioning
confidence: 93%
“…Most randomized control trials (RCTs) have different protocols, patient populations, sham mechanisms, outcome definitions/measurements, and follow up. In an attempt to answer questions about the utility of LiSWT for ED there have been a large number of RCTs published in the last 10 years, as well as approximately 10 meta-analysis studies in about the last 7 years [ 13 14 15 16 17 18 19 20 21 22 ].…”
Section: Main Bodymentioning
confidence: 99%
“…Specific patient populations have been evaluated via a meta-analysis approach, with a 2022 study reporting on the effects of LiSWT on ED for post-prostatectomy patients. The meta-analysis showed that in the 4 studies reporting IIEF scores at 3 months, there was a weighted mean difference of 2.04 (95% CI: –3.72 to –0.35; p=0.02) favoring the treatment group [ 20 ].…”
Section: Main Bodymentioning
confidence: 99%
“…Therefore, to analyze these conflicting results, meta-analyses of RCTs on Li-ESWT for ED have been published ( Table 4 ) [ 86 87 88 89 90 91 ]. First, a total of 833 patients from 14 studies were included in the meta-analysis published by Lu et al [ 86 ], which showed that patients who underwent Li-ESWT had significantly improved IIEF (weighted mean difference [WMD]: 2.00; 95% confidence interval [CI], 0.99–3.00; p<0.0001) and EHS (risk difference: 0.16; 95% CI, 0.04–0.29; p=0.01) scores compared with the control.…”
Section: Preclinical Research Of Ed Biotherapymentioning
confidence: 99%